Molecular detection of picornaviruses in diarrheic small ruminants at a glance: enterovirus, hunnivirus, and kobuvirus in türkiye - Ilke KARAYEL-HACIOGLU; Selda DURAN-YELKEN; Feray ALKAN (Kafkas Universitesi Veteriner Fakültesi Dergisi, 2022)
Enteric diseases are considered an important factor aff ecting the livestock industry; however, there are limited data on viruses that cause enteric diseases in small ruminants in our country. In this study, we focused on enterovirus (EV), hunnivirus (HuV), and kobuvirus (KoV), which are members of the family of Picornaviridae. In order to provide further information on the prevalence and the molecular epidemiology of these viruses, a total of 73 fecal samples or gut contents from diarrheic sheep and goats were screened for EV, HuV, and KoV. For this purpose, RT-PCRs were performed by using the specific primers for each virus. Th e prevalence rate determined in the sampled population was 2.7% (2/73) for each virus. In detail, EVs (2/60, 3.3%) and HuVs (2/60, 3.3%) were each detected in only sheep samples while KoVs were identified in a goat sample (1/13, 7.6%) and a sheep sample (1/60, 1.6%). Th ere was no evidence of coinfection with these viruses in the tested animals. According to the results of the molecular analyzes, our EVs were clustered in caprine/ovinespecific EV-G and HuV strains retrieved in this study were grouped along with the other caprine/ovine origin sequences in Hunnivirus A2 genotype. Moreover, it was observed that the detected KoVs clustered in distinct species: Aichivirus B and Aichivirus C. In conclusion, this study, which reported the detection of EVs and HuVs from sheep as well as KoVs from sheep and goats in our country, provides valuable data on the epidemiology and molecular characteristics of these viruses.